BLOCKCHAIN-BASED WAQF MANAGEMENT: A SHARIA-COMPLIANT INNOVATION FOR TRANSPARENT GOVERNANCE IN MALAYSIA - Zain Nizam; Rashid Rahman; Aiman Fariq (Yayasan Adra Karima Hubbi, 2025)
The governance of waqf institutions in Malaysia has faced persistent challenges related to transparency, accountability, and public trust. Traditional waqf management practices often lack systematic reporting, real-time monitoring, and effective stakeholder engagement, leading to inefficiencies and potential misuse of assets. In response to these issues, this study explores the implementation of blockchain technology as an innovative and Sharia-compliant solution to enhance waqf governance. The aim of this research is to examine the potential of blockchain-based systems to provide transparent, immutable, and decentralized management mechanisms for waqf assets within the Malaysian context. Employing a qualitative methodology, data were gathered through interviews with Islamic finance experts, waqf practitioners, and blockchain developers, complemented by document analysis of regulatory frameworks and case studies. The findings indicate that blockchain technology can significantly improve waqf transparency, traceability of donations, and real-time auditability, while ensuring compliance with Islamic legal principles. However, successful adoption requires legal reform, stakeholder digital literacy, and standardized technical frameworks. This research contributes to the evolving discourse on Islamic financial innovation, highlighting the transformative potential of blockchain for ethical and transparent asset management in Muslim societies.